Global Indigeneities and the Environment - Karen L. Thornber (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
Global Indigeneities and the Environment-covering fields from American Indian Studies, anthropology, communications, ethnoecology, ethnomusicology, geography, global studies, history, and literature, the purpose of the Special Issue is to give new understandings of the concept of global indigeneities and to showcase some of the most promising work in the field to date.